Muslims in the West : from sojourners to citizens - Haddad, Yvonne Yazbeck, 1935- (Oxford University Press, 2002)
Muslims are the second largest religious group in much of Europe and North America. The essays in this collection look both at the impact of the growing Muslim population on Western societies and how Muslims are adapting to life in the West.